A method for preparing a lead-acid battery negative plate without chemical formation using waste lead paste as raw material

By mixing waste lead paste with carbon material and performing constant current electrolysis in the sulfate system, efficient recycling of waste lead paste and direct preparation of lead-acid battery negative electrode plates are achieved, and the energy consumption of waste lead paste recovery in the prior art is solved. High and serious pollution problems, and avoid the "floating carbon phenomenon" and improve battery performance.

CN116247170BActive Publication Date: 2025-02-25KUNMING UNIV OF SCI & TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310175550.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-28
Publication Date
2025-02-25
Estimated Expiration
2043-02-28

AI Technical Summary

Technical Problem

In the prior art, the process of recycling lead by waste lead paste has problems such as high energy consumption, serious pollution and inability to substantially recover. At the same time, the "floating carbon phenomenon" caused by the large density difference between lead and carbon in lead-carbon batteries affects battery performance.

Method used

After mixing waste lead paste with carbon material, constant current electrolysis is performed in the sulfate system. Solid phase reduction is carried out by introducing additives, leading to in situ reduction into porous sponge lead, deposited on the surface of carbon material to form lead-carbon composite material, and directly prepared The negative electrode plate of lead-acid battery without chemical transformation.

Benefits of technology

It realizes efficient recycling of waste lead paste and direct preparation of lead-acid battery negative electrode plates, avoids traditional curing and decomposition steps, is simple in process, low in cost, and solves problems such as "floating carbon phenomenon", improving battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116247170B_ABST
    Figure CN116247170B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a lead-acid battery negative plate without formation using waste lead paste as a raw material, and belongs to the technical field of lead resource recovery. The present invention mixes waste lead paste with a carbon material and then applies it to a lead alloy negative grid, performs constant current electrolysis in a sulfate system, introduces an additive into the electrolyte during cathode reduction for solid phase reduction, induces the lead in the lead-containing waste lead paste to be in situ reduced and deposited on the surface of the additive including the carbon material in the form of porous sponge lead to form a lead-carbon composite layer, and directly obtains a lead-acid battery negative plate without formation. The lead-acid battery negative plate of the present invention can be directly assembled with a commercial positive plate to obtain a standard lead-acid battery, and can be directly used as a lead-acid battery negative electrode without going through the curing and formation steps of a traditional lead-acid battery, and has the advantages of simple process and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a lead-acid battery negative plate without chemical formation by using waste lead paste as a raw material, belonging to the technical field of lead resource recovery. Background Art

[0002] As the demand for lead-acid batteries grows, the lead waste released by lead-acid batteries will also continue to increase, and the recovery of lead secondary resources will become a global concern. Therefore, the recycling of waste lead-acid batteries has become increasingly important. The waste lead paste produced by waste lead-acid batteries contains components such as PbSO4, PbO2, PbO and Pb, which are difficult to recycle. Therefore, the key is to achieve the recovery of lead resources in waste lead paste.

[0003] At present, the mainstream process technology for smelting waste lead paste at home and abroad mainly includes pyrometallurgical technology and hydrometallurgical technology. The traditional waste lead paste recovery technology based on pyrometallurgical process has high energy consumption and will produce a large amount of lead compounds, lead slag, trace elements and lead dust and other pollution. There are serious hazards to environmental pollution and the health of operators. Compared with the pyrometallurgical process, the hydrometallurgical process has the advantages of clean process and high comprehensive resource utilization rate. In the prior art, lead dioxide, lead oxide and lead powder are first oxidized and reduced to lead perchlorate or lead methanesulfonate solution, filtered, and the filter residue component is mainly lead sulfate, and then lead is recovered by electrolytic deposition. Alternatively, the lead paste is added to an acid reactor containing a catalyst to cause the lead and lead dioxide in the lead paste to undergo an oxidation-reduction reaction to obtain a soluble lead salt solution. At the same time, lead oxide also reacts with the acid solution to obtain lead salt. After separation, a soluble lead salt solution and an insoluble filter residue with lead sulfate as the main component are obtained. After the lead salt solution is electrolyzed, lead, oxygen and an acidic electrolyte are obtained. Alternatively, water, sulfuric acid and lead paste are added to the reaction tank, and then hydrogen peroxide is added to the reaction tank, and the reaction is carried out for 2 hours; filter to obtain reduced slag; then mix the reduced slag with lead powder to make a mixture, apply the mixture to the cathode basket, and add electrolyte to the electrolytic tank; electrolyze at room temperature for 35 to 95 hours to obtain electrolytic lead; take the electrolytic lead out of the cathode basket, make lead agglomerates, and refine to obtain refined lead ingots. The above technical solution has the disadvantages of long processing flow, high reagent consumption and high energy consumption through conversion-leaching-electrodeposition method, and in strong acid or strong alkaline system, the equipment is corroded greatly, and lead sulfate cannot be converted into metallic lead, and the substantial recovery of waste lead paste is still not achieved, which limits its commercial application.

[0004] Lead-acid batteries need to be dried and solidified into green plates during the manufacturing process. Drying and solidification is generally carried out under a certain oxygen content and temperature in order to improve the mechanical strength and electrochemical properties of the plates after formation. Then, the plates are obtained through the formation step. The formation step is to immerse the green plates in a dilute sulfuric acid solution for electrolysis. After oxidation and reduction, the negative plates are converted into electrochemically active Pb. This stage consumes a lot of electrical energy for the reduction of lead oxide to lead. In recent years, lead-acid batteries have been upgraded to new lead-carbon batteries due to their outstanding performance and advantages. However, the density of carbon materials is quite different from that of lead. The physical mixing of the two is prone to the "floating carbon phenomenon", which affects the affinity and connection structure between them. Summary of the invention

[0005] The present invention aims at the problems of recovering lead from waste lead paste in the prior art and the "floating carbon phenomenon" caused by the large difference in density between lead and carbon in lead-carbon batteries, and proposes a method for preparing a lead-acid battery negative plate without formation using waste lead paste as a raw material, that is, the waste lead paste is mixed with a carbon material and then coated on a lead alloy negative grid, and constant current electrolysis is performed in a sulfate system, and an additive is introduced into the electrolyte during cathode reduction for solid phase reduction, so as to induce the lead in the lead-containing waste lead paste to be reduced in situ to porous sponge lead, and the porous sponge lead is deposited on the surface of the carbon material to form a lead-carbon composite material, and a lead-acid battery negative plate without formation is directly obtained. The lead-acid battery negative plate of the present invention can be directly assembled with a commercial positive plate to obtain a standard lead-acid battery, and can be directly used as a lead-acid battery negative electrode without going through the curing and formation steps of a traditional lead-acid battery, and has the advantages of simple process and low cost.

[0006] A method for preparing a lead-acid battery negative plate without chemical formation using waste lead paste as a raw material, the specific steps are as follows:

[0007] (1) peeling the waste lead paste from the waste lead-acid battery, and then washing, drying and grinding in sequence to obtain the waste lead paste powder;

[0008] (2) mixing waste lead paste powder, barium sulfate, sodium lignin sulfonate, short fibers, humic acid and additives to obtain a waste lead paste mixture, adding deionized water to the waste lead paste mixture and stirring to form a waste lead paste slurry;

[0009] (3) coating the waste lead paste slurry on the lead alloy grid current collector, drying and curing to obtain the waste lead paste plate;

[0010] (4) Using the waste lead paste plate as the cathode and the anode as a graphite anode, a lead alloy anode or a titanium-based coated anode, constant current electrolysis is carried out in a sulfate system electrolyte, and the lead-containing substances in the waste lead paste are converted in situ into porous sponge lead to obtain a lead-acid battery negative plate that does not require chemical formation.

[0011] Based on the mass of the waste lead paste powder as 100%, the waste lead paste mixture in step (2) contains 0.5-1.0% barium sulfate, 0.2-0.5% sodium lignin sulfonate, 0.05-0.2% short fibers, 0.3-0.8% humic acid, and 0.1-2.0% additives.

[0012] The short fiber is a general term in lead-acid batteries, including polyester fiber, polypropylene fiber, polyacrylonitrile fiber, nylon fiber, polyethylene fiber, polyamide fiber and other organic fibers. The function of the short fiber is to connect the active material, prevent cracking during the curing process, and enhance the mechanical strength of the plate. Polypropylene short fiber can be selected according to the acid and alkali resistance, with a length of 1-4mm.

[0013] The additive in step (2) contains carbon material, and the carbon material is one or more of biomass-derived carbon material, graphite, carbon nanotubes, graphene, acetylene black, polyaniline, and polythiophene, and the carbon material accounts for 0.1-2.0 wt%.

[0014] Preferably, the additive in step (2) further contains metal oxide, which is one or more of zinc oxide, titanium dioxide, and manganese dioxide, and the metal oxide accounts for 0-5.0 wt%.

[0015] The sulfate system in step (4) contains a conductive salt and an additive, wherein the conductive salt is one or more of ammonium sulfate, sodium sulfate, potassium sulfate, and magnesium sulfate, and the additive is one or more of amines, alcohols, imidazoles, amino acids, amine derivatives, alcohol derivatives, imidazole derivatives, and amino acid derivatives.

[0016] The concentration of the conductive salt in the sulfate system is 20-40 g / L, the amount of the additive added is 1.0-10.0 wt % of the solution mass, and the pH value of the sulfate system is 5.5-9.5.

[0017] The inter-electrode distance of the constant current electrolysis in step (4) is 3-15 cm, the electrolysis temperature is 30-60° C., and the current density is 200-800 A / m 2 , the electrolysis time is 2-12h.

[0018] In the step (4), the lead in the negative plate of the lead-acid battery is in situ deposited on the surface of the additive including the carbon material in the form of porous sponge lead to form a lead-carbon composite layer.

[0019] The solid phase electrolysis principle of waste lead paste of the present invention is:

[0020] Cathode reaction:

[0021] Anode reaction:

[0022] After the additive is added to the sulfate system electrolyte, the cathode polarization is enhanced and the cathode hydrogen evolution overpotential is increased, thereby increasing the solid phase electrolysis nucleation rate of waste lead paste, increasing the in-situ direct reduction of lead compounds to lead, and reducing the amount of hydrogen evolution. Therefore, the additive can improve the current efficiency and reduce energy consumption.

[0023] The beneficial effects of the present invention are:

[0024] (1) The present invention introduces special additives into waste lead paste to construct a conductive network and reduce the cell voltage to achieve the purpose of energy saving, consumption reduction and efficiency improvement;

[0025] (2) The electrolyte additives in the electrolysis process of the present invention can adjust the solid-phase reduction process of the lead compound, induce the in-situ reduction of the lead in the lead-containing waste lead paste into a qualified porous sponge lead, and the porous sponge lead is deposited on the surface of the carbon material to form a lead-carbon composite material, and a lead-acid battery negative plate without formation is directly obtained, thereby avoiding the formation step of the lead-acid battery. The solid-phase electroreduction of the present invention has the advantages of simple process, small footprint, low investment, high lead recovery rate, clean process, etc., and avoids the disadvantages of strong corrosion of the reaction system.

[0026] (3) The lead-acid battery negative electrode plate of the present invention can be directly assembled with a commercial positive electrode plate to obtain a standard lead-acid battery, without going through the curing and formation steps of a traditional lead-acid battery, and can be directly used as the negative electrode of the lead-acid battery, which has the advantages of simple process and low cost;

[0027] (4) The present invention can convert all lead-containing components in waste lead paste into high-purity sponge lead without any pre-treatment, and the synthesized lead-carbon composite negative electrode plate does not require further curing and chemical formation treatment, which not only solves the resource recovery problem of waste lead paste, but also realizes the effect of directly converting waste lead paste into lead-carbon battery negative electrode plate, simplifies the secondary treatment of recycled lead and the cumbersome curing and chemical formation process of lead-carbon battery negative electrode, and also solves the problems of "floating carbon phenomenon" easily occurring in physical mixing, affinity and connection structure;

[0028] (5) The present invention achieves no waste residue storage and no waste gas or wastewater discharge. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a diagram of a solid-phase electrolysis device for waste lead paste according to the present invention;

[0030] Figure 2 The test performance diagram of assembling a 12V100Ah lead-acid battery using the lead-acid battery negative plate of Example 3 under 10 hour rate and 120 hour rate conditions;

[0031] Figure 3 This is a test diagram of the internal resistance of a 12V100Ah lead-acid battery assembled using the lead-acid battery negative plate of Example 3 during the cycle process. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.

[0033] Embodiment 1: A method for preparing a lead-acid battery negative plate without chemical formation using waste lead paste as raw material, the specific steps are as follows:

[0034] (1) peeling the waste lead paste from the waste lead-acid battery, and then washing, drying and grinding in sequence to obtain the waste lead paste powder;

[0035] (2) mixing waste lead paste powder, barium sulfate, sodium lignin sulfonate, short fibers, humic acid and an additive (activated carbon from mulberry branches) to obtain a waste lead paste mixture, and adding deionized water to the waste lead paste mixture and stirring to form a waste lead paste slurry; based on the mass of the waste lead paste powder as 100%, the waste lead paste mixture in step (2) contains 0.8% barium sulfate, 0.25% sodium lignin sulfonate, 0.1% short fibers, 0.5% humic acid and 0.5% additive (activated carbon from mulberry branches);

[0036] (3) coating 19 g of waste lead paste slurry on the lead-calcium-tin alloy grid current collector, drying and curing to obtain a waste lead paste electrode plate;

[0037] (4) Using waste lead paste plates as cathodes and Ti / RuO2-TiO2 plates as anodes, constant current electrolysis is carried out in a sulfate system electrolyte, and the lead-containing substances in the waste lead paste are in situ converted into porous sponge lead to form a porous sponge lead-carbon composite material containing mulberry branch activated carbon to obtain a lead-acid battery negative electrode plate that does not require chemical formation; wherein the sulfate system contains 50 g / L of conductive salt ammonium sulfate and 2.0 wt% of additive ethylene glycol, the pH value of the sulfate system is 6.0, the inter-electrode spacing of the constant current electrolysis is 5 cm, the electrolysis temperature is 40 ° C, and the current density is 300 A / m 2 , electrolysis time is 5h;

[0038] The dried porous sponge lead negative electrode plate containing activated carbon from mulberry branches and the conventionally formed positive electrode plate were assembled into a 2V2Ah battery in a 2-negative 3-positive mode, sulfuric acid electrolyte was injected, and the discharge capacity was directly tested after standing for 3 hours.

[0039] In this embodiment, the lead recovery rate is 87.5%, the energy consumption is 756.8 kWh, and the current efficiency is 84.3%. The synthesized negative plate is assembled into a 2V2Ah battery with a capacity of 156.1 mAh / g.

[0040] Embodiment 2: A method for preparing a lead-acid battery negative plate without chemical formation using waste lead paste as raw material, the specific steps are as follows:

[0041] (1) peeling the waste lead paste from the waste lead-acid battery, and then washing, drying and grinding in sequence to obtain the waste lead paste powder;

[0042] (2) mixing waste lead paste powder, barium sulfate, sodium lignin sulfonate, short fibers, humic acid and additives (mulberry branch activated carbon and conductive polyaniline) to obtain a waste lead paste mixture, adding deionized water to the waste lead paste mixture and stirring to form a waste lead paste slurry; based on the mass of the waste lead paste powder as 100%, the waste lead paste mixture in step (2) contains 0.75% barium sulfate, 0.3% sodium lignin sulfonate, 0.1% short fibers, 0.6% humic acid, 0.5% additive (mulberry branch activated carbon) and 1.0% additive (conductive polyaniline);

[0043] (3) coating 19 g of waste lead paste slurry on the lead-calcium-tin alloy grid current collector, drying and curing to obtain a waste lead paste electrode plate;

[0044] (4) Using waste lead paste plates as cathodes and Ti / RuO2-TiO2 plates as anodes, constant current electrolysis is carried out in a sulfate system electrolyte, and the lead-containing substances in the waste lead paste are in situ converted into porous sponge lead to form a porous sponge lead-carbon composite material containing mulberry branch activated carbon and conductive polyaniline to obtain a lead-acid battery negative electrode plate that does not require chemical formation; wherein the sulfate system contains a conductive salt ammonium sulfate with a concentration of 50 g / L and an additive ethylene glycol with a mass fraction of 2.0 wt%, the pH value of the sulfate system is 6.0, the inter-electrode spacing of the constant current electrolysis is 6 cm, the electrolysis temperature is 30 °C, and the current density is 400 A / m 2 , electrolysis time is 5h;

[0045] The dried porous sponge lead negative electrode plate containing mulberry branch activated carbon and conductive polyaniline and the conventionally formed positive electrode plate were assembled into a 2V2Ah battery in a 2-negative 3-positive mode, and sulfuric acid electrolyte was injected. After standing for 3 hours, the discharge capacity was directly tested.

[0046] In this embodiment, the lead recovery rate is 85.2%, the energy consumption is 732.1 kWh, and the current efficiency is 87.8%. The synthesized negative electrode plate is assembled into a 2V2Ah battery with a capacity of 163.6 mAh / g.

[0047] Embodiment 3: A method for preparing a lead-acid battery negative plate without chemical formation using waste lead paste as raw material, the specific steps are as follows:

[0048] (1) peeling the waste lead paste from the waste lead-acid battery, and then washing, drying and grinding in sequence to obtain the waste lead paste powder;

[0049] (2) mixing waste lead paste powder, barium sulfate, sodium lignin sulfonate, short fibers, humic acid and an additive (coconut shell activated carbon) to obtain a waste lead paste mixture, adding deionized water to the waste lead paste mixture and stirring to form a waste lead paste slurry; based on the mass of the waste lead paste powder as 100%, the waste lead paste mixture in step (2) contains 0.8% barium sulfate, 0.4% sodium lignin sulfonate, 0.1% short fibers, 0.6% humic acid and 1.5% additive (mulberry branch activated carbon);

[0050] (3) coating 19 g of waste lead paste slurry on the lead-calcium-tin alloy grid current collector, drying and curing to obtain a waste lead paste electrode plate;

[0051] (4) Using waste lead paste plates as cathodes and Ti / RuO2-TiO2 plates as anodes, constant current electrolysis is carried out in a sulfate system electrolyte, and the lead-containing substances in the waste lead paste are in situ converted into porous sponge lead to form a porous sponge lead-carbon composite material containing coconut shell activated carbon to obtain a lead-acid battery negative plate that does not require chemical formation; wherein the sulfate system contains 50 g / L of conductive salt ammonium sulfate and 1.0 wt% of additive ethylenediamine, the pH value of the sulfate system is 8.5, the inter-electrode spacing of the constant current electrolysis is 4 cm, the electrolysis temperature is 30 °C, and the current density is 300 A / m 2 , electrolysis time is 6h;

[0052] The dried porous sponge lead negative plate containing coconut shell activated carbon and the conventionally formed positive plate were assembled into 2V2Ah and 12V100Ah lead-acid batteries, sulfuric acid electrolyte was injected, and the discharge capacity was directly tested after standing for 3 hours;

[0053] In this example, the lead recovery rate is 92.5%, the energy consumption is 625.4 kWh, and the current efficiency is 89.8%. The synthesized negative plate is assembled into a 2V2Ah battery with a capacity of 195.4 mAh / g;

[0054] The performance graphs for 10 hour rate and 120 hour rate are shown in Figure 2 ,from Figure 2 It can be seen that the discharge time of the battery at the 10-hour rate is 705 minutes, and the discharge time of the battery at the 120-hour rate is 9160 minutes, both exceeding the rated discharge time of the battery;

[0055] Internal resistance stability test during battery cycling Figure 3 ,from Figure 3 It can be seen that during the first 250 cycles, the internal resistance of the assembled battery remained at a low level, showing good stability.

[0056] Example 4: A method for preparing a lead-acid battery negative plate without chemical formation using waste lead paste as raw material, the specific steps are as follows:

[0057] (1) peeling the waste lead paste from the waste lead-acid battery, and then washing, drying and grinding in sequence to obtain the waste lead paste powder;

[0058] (2) mixing waste lead paste powder, barium sulfate, sodium lignin sulfonate, short fibers, humic acid and additives (graphite and titanium oxide) to obtain a waste lead paste mixture, adding deionized water to the waste lead paste mixture and stirring to form a waste lead paste slurry; based on the mass of the waste lead paste powder as 100%, the waste lead paste mixture in step (2) contains 0.8% barium sulfate, 0.4% sodium lignin sulfonate, 0.1% short fibers, 0.5% humic acid, 1.0% additive (graphite) and 0.5% additive (titanium oxide);

[0059] (3) coating 19 g of waste lead paste slurry on the lead-calcium-tin alloy grid current collector, drying and curing to obtain a waste lead paste electrode plate;

[0060] (4) Using waste lead paste plates as cathodes and Ti / RuO2-TiO2 plates as anodes, constant current electrolysis is carried out in a sulfate system electrolyte, and the lead-containing substances in the waste lead paste are in situ converted into porous sponge lead to form a porous sponge lead-carbon composite material containing graphite and titanium oxide to obtain a lead-acid battery negative electrode plate that does not require chemical formation; wherein the sulfate system contains a conductive salt ammonium sulfate with a concentration of 50 g / L and an additive ethylenediamine with a mass fraction of 1.0 wt%, the pH value of the sulfate system is 8.5, the inter-electrode spacing of the constant current electrolysis is 6 cm, the electrolysis temperature is 35 °C, and the current density is 400 A / m 2 , electrolysis time is 4h;

[0061] The dried porous sponge lead negative electrode plate containing graphite and titanium oxide and the conventionally formed positive electrode plate were assembled into a battery in a 2-negative 3-positive mode, sulfuric acid electrolyte was injected, and the discharge capacity was directly tested after standing for 3 hours;

[0062] In this embodiment, the lead recovery rate is 97.3%, the energy consumption is 716.8 kWh, and the current efficiency is 82.8%. The synthesized negative plate is assembled into a 2V2Ah battery with a capacity of 175.5 mAh / g.

[0063] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A method for preparing a lead-acid battery negative plate without chemical formation using waste lead paste as raw material, characterized in that: The specific steps are as follows: (1) peeling the waste lead paste from the waste lead-acid battery, and then washing, drying and grinding in sequence to obtain the waste lead paste powder; (2) mixing waste lead paste powder, barium sulfate, sodium lignin sulfonate, short fibers, humic acid and additives to obtain a waste lead paste mixture, adding deionized water to the waste lead paste mixture and stirring to form a waste lead paste slurry; the additive contains a carbon material and a metal oxide; the carbon material is one or more of a biomass-derived carbon material, graphite, carbon nanotubes, graphene, acetylene black, polyaniline, and polythiophene; the metal oxide is one or more of zinc oxide, titanium dioxide, and manganese dioxide; (3) coating the waste lead paste slurry on the lead alloy grid current collector, drying and curing to obtain the waste lead paste plate; (4) Using the waste lead paste plate as the cathode and the anode as a graphite anode, a lead alloy anode or a titanium-based coating anode, constant current electrolysis is carried out in a sulfate system electrolyte, and the lead-containing substances in the waste lead paste are in situ converted into porous sponge lead to obtain a lead-acid battery negative plate that does not require chemical conversion; the sulfate system contains a conductive salt and an additive, the conductive salt is one or more of ammonium sulfate, sodium sulfate, potassium sulfate, and magnesium sulfate, and the additive is one or more of amine, alcohol, imidazole, amino acid, amine derivative, alcohol derivative, imidazole derivative, and amino acid derivative; the concentration of the conductive salt in the sulfate system is 20-40g / L, the amount of the additive added is 1.0-10.0wt% of the solution mass, and the pH value of the sulfate system is 5.5-9.5; the inter-electrode spacing of the constant current electrolysis is 3-15cm, the electrolysis temperature is 30-60℃, and the current density is 200-800A / m 2 , the electrolysis time is 2-12h; the lead in the negative plate of the lead-acid battery is in situ deposited on the surface of the additive including the carbon material in the form of porous sponge lead to form a lead-carbon composite layer.

2. The method for preparing a lead-acid battery negative plate without chemical formation using waste lead paste as raw material according to claim 1, characterized in that: Based on the mass of the waste lead paste powder as 100%, the waste lead paste mixture in step (2) contains 0.5-1.0% barium sulfate, 0.2-0.5% sodium lignin sulfonate, 0.05-0.2% short fibers, 0.3-0.8% humic acid, and 0.1-2.0% additives.

3. The method for preparing a lead-acid battery negative plate without chemical formation using waste lead paste as raw material according to claim 2, characterized in that: Based on the mass of the waste lead paste powder being 100%, the carbon material of the additive accounts for 0.1-2.0wt%.

4. The method for preparing a lead-acid battery negative plate without chemical formation using waste lead paste as raw material according to claim 3, characterized in that: The metal oxide of the additive accounts for 0.5wt%.

Citation Information

Patent Citations

  • Preparation method of lead storage battery negative plate by using lead-containing compound in waste lead storage battery as raw material

    CN105244563A

  • Recycling method of solid-phase electrolysis regenerated lead of waste lead acid accumulator

    CN110656352A